Experimental study of dexamethasone-loaded hollow hydroxyapatite microspheres applied to direct pulp capping of rat molars - Liu, Xiaoli; Xie, Yuandong; Gao, Weijia; Zhan, Luoning; Hu, Ling; Zuo, Linjing; Li, Yi (Frontiers in Endocrinology, 2023)
Background: Dexamethasone (DEX) exerts anti-inflammatory and osteogenic effects. Hydroxyapatite is commonly used in bone repair due to its osteoconductivity, osseointegration, and osteogenesis induction. Hollow hydroxyapatite (HHAM) is often used as a drug carrier.Objective: This study aimed to investigate the histological responses of exposed dental pulp when dexamethasone-loaded nanohydroxyapatite microspheres (DHHAM) were used as a direct capping agent. Methods: Cavities were created in the left maxillary first molar of Wistar rats and filled with Dycal, HHAM, and DHHAM. No drug was administered to the control group. The rats were sacrificed at 1, 2, and 4 weeks after the procedure. The molars were extracted for fixation, demineralization, dehydration, embedding, and sectioning. H&E staining was performed to detect the formation of reparative dentin. H&E and CD45 immunohistochemical staining were performed to detect pulp inflammation. Immunohistochemical staining was performed to assess the expressions of dentin matrix protein 1 (DMP-1), interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-1β.The results of H&E and CD45 immunohistochemical staining showed that the degree of inflammation in the DHHAM group was less than that in the Control and HHAM groups at 1, 2, and 4 weeks after capping of the rat molar teeth (p<0.01). The H&E staining showed that the percentage of reparative dentin formed in the DHHAM group was higher than that in the Control, HHAM (p<0.001), and Dycal groups (p<0.01) at 1 and 2 weeks, and was significantly higher than that in the Control group (p<0.001) and the HHAM group (p<0.01) at 4 weeks. The immunohistochemical staining showed a lower range and intensity of expression of IL-1β, IL-6, and TNF-α and high expression levels of DMP-1 in the DHHAM group at 1, 2, and 4 weeks after pulp capping relative to the Control group. Conclusions: DHHAM significantly inhibited the progression of inflammation and promoted reparative dentin formation.